FISCAL MANAGEMENT IN MUNICIPALITIES PARANAENSES: A SPATIAL ANALYSIS - Marconato, Marcio (2016)
The aim of this paper was to establish a spatial analysis of the Fiscal Management Index (RGF) and check their relationship with the Municipal Development Index (FMDI), in the municipalities of the state of Paraná. The increase in public spending, given the context of budgetary constraints, has not been sufficient to attend to primary needs of companies, undermining the services offered by the government. The methodology was based on exploratory spatial data analysis through Global and Local studies, considering the years of 2006, 2009 and 2013. The sources consulted were the Federation of Industries of the State of Rio de Janeiro (FIRJAN), the Brazilian Institute of Geography and Statistics (IBGE) and the Paraná Institute for Economic and Social Development (IPARDES). The results showed that the vast majority of municipalities showed IGF on condition of difficulty or critical, 55% of municipalities had IGF above average. The number of municipalities with excellent level of development increased in the period and more than 50% of the units presented FMDI above average. The global Moran coefficient pointed out the existence of positive spatial autocorrelation of the IGF. The clusters with high IGF have been identified in the regions West and metropolitan region of Curitiba and clusters with low IGF in the Northwest. The positive autocorrelation between IGF and FMDI was found in all the years analyzed. The West, Northwest and metropolitan region of Curitiba shelter the high clustered IGF and IFDM, while North region accommodated the low-low clusters.